The Efficiency of Different Methods of Lime Application During Soil Preparation - Saayman, D.; van Huyssteen, L. (South African Journal of Enology and Viticulture, 2017)
The efficiency of a newly developed lime applicator, mounted on different soil preparation implements and in combination with different methods of lime application, was studied. The distribution and placement of lime were tracked by using fluorescent pigments mixed with the lime, and subsequent photography under UV light. It was found that lime, applied on the surface before the deep-ploughing operation, gave surprisingly good results in comparison .to blown-in lime, or conventional methods, but that the lime applicator in combination with a winged plough, needs modification. Double ploughing the soil seems to be an efficient method of ensuring proper mixing of lime and soil.